Educação superior a distância: teia, tessitura para uma experimentação pedagógica - Karolesky, Mirian Ligia Endo (2015)
We live in the information age, when more and more people have extended advances and the availability of technological resources that have contributed to the development of different areas of human knowledge. In the context of the Education Distance, different technological resources are being used to carry Degree courses to the far corners of Brazil, seeking a non-linear learning model based on hypertextuality, transdisciplinary and transversality . The question we ask is: whether or not this type of education influencing the training of teachers whose practice is focused on the future, for a hypertextual transverse education, supported by new technology, running from na arboreous model of teaching? The research is based on philosophical reflections of Deleuze and Guattari, who present the concept of rhizome as opposed to a tree concept to conceptualize knowledge. Anchor us, yet, in the view of Lévy, Morin, Dal Molin, Nicolescu, Catapan, Costa, Moran and other researchers may weave for our text about the use of technology in education. For the development of analysis proposed in this study, we selected two Virtual Learning Environments Education (AVEA) to observe how the contents are worked, are assumed, or not a rhizomatic approach to education,that is a way of working content so relevant to our time, and the wishes of oriented training to a full citizen life, and we did a survey of the academic courses degrees, making sure that the distance mode mediated by the intense use of digital communication technologies influence the practice of future professionals of education at a time of its stages teachers. The research showed that the Distance education is configured as a way that allows different lines of escape from the Cartesian model of education, and that despite still has remnants of the traditional model, show as an excellent chance to break the horizons in new experimentations and thereby meet the desires of a society inserted in technological era.The environments defined in this proposal are as Blackboard and Moodle platforms, and selected institutions were universities the context of the Open University of Brazil (UAB) pole Goioerê, namely the State University of Ponta Grossa (UEPG), where we act as tutor, and University Paulista (UNIP), of a private nature, with courses offered by the pole Goioerê in which we operate as a coordinator, tutor and researcher